Social media engagement on MSMEs business performance: A systematic review - Abdol Ghapar, Marha; Luqman, Azyanee; Ismail, Mohd Nasir (Journal of Islamic, Social, Economics and Development, 2025)
Social media has become an important part of marketing strategy for micro, small, and medium enterprises (MSMEs), as it offers a cost-effective way to reach a larger audience base besides allowing engagement with customers in such brief period of time. Social media can significantly influence the performance of MSMEs in terms of brand awareness, customer satisfaction, sales, and many more. However, more systematic studies should be done to uncover the elements contributing towards business performance in the social media scenario. This study aims to systematically review past literatures that have been done in the social media engagement towards business performance scene. This systematic review is guided by ROSES review protocol. From the initial results of 252 records, only 22 relevant articles in line with the study’s objective were selected. Majority of the studies were done in developing countries. Elements under the engagement variable include sales/promotion, user-generated content, firm-generated content, comments, likes, shares, customer relationship, and communication; while for the performance variable, keywords were grouped into elements of financial and non-financial performance.